Exploring the faculty’s selection of teaching methods in International Relations: Case of Azerbaijan - Arazzada, Farid; Hasanova, Sabina (ADA University, 2023)
The learning-centered teaching presupposes an approach oriented in the long-lasting learning of the student combining the lecture and active learning methods considering the student’s learning needs and learning objectives of the course. Previous domestic research suggests that the implementation of active learning methods in higher educational institutions present challenges for the instructors for the reasons such as low level of engagement of students, lack of technical facilities, and instructor’s lack of capabilities in integration of innovative methods. The preliminary data collected from the graduates of International Relations (IR) program from three universities in Baku suggest that lecture-based learning still persists in the classes. Therefore, the study investigated the applied teaching methods in IR program and identified the factors contributing to the faculty’s teaching decision-making process. The qualitative research design was employed, whereby fourteen instructors instructing courses related to International Relations at University A, University B, and University C were interviewed, and their syllabuses were previewed. The findings responding to the first research question displays that the instructors favor the integration of active learning methods in classes, as they motivate students, and enable them to develop collaborative, writing, analytical thinking skills. The data related to the second research question suggest that philosophical assumptions, student-related factors, the instructor’s involvement in professional growth, course content, and the institutional factors influence faculty’s decision on selecting particular methods. Substantially, the philosophical beliefs of the instructor and student-related factors are revealed to have an effect on the decision-making process of the instructor by either inhibiting or fostering application of learning-centered approach. Based on the findings of the study and literature review, the guideline on learning-centered teaching is presented that incorporates the learning-centered concept, teaching methods, and Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. It is believed that the guideline may address the student-related challenges and help the instructors to make effective decisions enhancing student’s learning.
Keywords: Active learning -- Azerbaijan; Student-centered learning; College teaching -- Methodology; Education